2015
DOI: 10.1007/s00253-015-6382-y
|View full text |Cite
|
Sign up to set email alerts
|

The herbal-derived honokiol and magnolol enhances immune response to infection with methicillin-sensitive Staphylococcus aureus (MSSA) and methicillin-resistant S. aureus (MRSA)

Abstract: The emergence of antibiotic resistant strains such as methicillin-resistant Staphylococcus aureus (MRSA) reminds us an urgent need to develop a new immune-modulating agent for preventing S. aureus infection. In this study, we found that herbal medicines, honokiol and magnolol, caused a significant cellular immune modulatory effect during S. aureus infection. In mouse macrophages, these compounds drove upregulation of an antioxidant effect in response to S. aureus, resulting in a dampened total cellular reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…Choi et al reported that honokiol and MG caused significant cellular immune-modulatory effect and decreased the production of ROS and inflammatory cytokines/ chemokines during S. aureus infection. Honokiol upregulated type I and III interferon mRNA expression in response to MSSA infection and inhibited the growth of MSSA at 2.5 μg ml −1 and MRSA at 5 μg ml −1 , whereas MG inhibited the growth of both bacterial cells at 5 μg ml −1 after 24 h of growing (Choi et al, 2015). MG and honokiol could inhibit S. mutans to prevent dental caries, with an MIC value of 10 μg ml −1 .…”
Section: Antibacterial Activitymentioning
confidence: 94%
“…Choi et al reported that honokiol and MG caused significant cellular immune-modulatory effect and decreased the production of ROS and inflammatory cytokines/ chemokines during S. aureus infection. Honokiol upregulated type I and III interferon mRNA expression in response to MSSA infection and inhibited the growth of MSSA at 2.5 μg ml −1 and MRSA at 5 μg ml −1 , whereas MG inhibited the growth of both bacterial cells at 5 μg ml −1 after 24 h of growing (Choi et al, 2015). MG and honokiol could inhibit S. mutans to prevent dental caries, with an MIC value of 10 μg ml −1 .…”
Section: Antibacterial Activitymentioning
confidence: 94%
“…In addition, magnolol significantly decreases ROS production and inflammatory cytokines expression in response to S. aureus in mouse macrophages. The internalization of S. aureus by human alveolar epithelial cells is also attenuated by magnolol [102]. Magnolol does not show any antagonistic effects on the 10 MRSA strains, when it is combined with the antibacterial agents synergistically.…”
Section: Clinical Prospectivementioning
confidence: 99%
“…In a separate study, O. stamineus extract also modulated the cellular immune response in vitro (Alshawsh et al, 2012). Similarly, the natural polyphenols isolated from Magnolia plant species, honokiol and magnolol, promoted a cellular immune response and slowed down C. elegans killing by S. aureus (Choi et al, 2015). …”
Section: Identification Of Novel Anti-infectivesmentioning
confidence: 99%